Garlic extract and hydrogen cyanamide on 'tupy' blackberry bud sprouting, flowering and harvest - Leonel, Sarita [UNESP]; Segantini, Daniela Mota [UNESP]; Tecchio, Marco Antonio [UNESP]; Ferreira, Rafael Bibiano [UNESP]; Azevêdo Souza, Jackson Mirellys [UNESP]; Ribeiro Auricchio, Marcelo Garcia [UNESP] (Southern Cross Publishing, 2016)
Considering the reduction of synthetic compounds used in sustainable fruit production system, this work aimed to evaluate and compare the effects of applying garlic extract and hydrogen cyanamide (C22H19Cl2NO3) in the bud sprouting, flowering and harvesting of blackberry. The research was conducted during the season of 2011 and 2012. The experiment design was randomized in split plots, consisting of 12 blocks. Each plot corresponded to the six treatments with hydrogen cyanamide, garlic extract and control (0%); and subplots were formed from the two crop seasons. 'Tupy' blackberry were 2 and 3 years-old, trained to 1.2m high espalier-type trellis with 4 lateral canes retained in a T configuration, with a spacing of 0.6 m between plants and 4.0 m between rows. The plants were pruned in August and the treatments applied immediately afterwards: 4% hydrogen cyanamide (standard product) and garlic extract in doses of 4.0%, 8.0%, 12.0% and 16.0%, and control. Both products were applied only once; and separately by using knapsack sprayer in the early morning hours. The hydrogen cyanamide 4% performed best, bringing forward more uniform bud sprouting and fruit harvesting. The intervals between: pruning and bud sprouting and pruning and harvesting were 14.5 and 87.5 days, respectively. The evaluated garlic extract concentrations showed similar values of production compared with the other treatments, except at 16% in 2011, being the highest concentration used on cultivated blackberry at São Manuel, São Paulo state, Brazil.
Keywords: Bud break; Climate adaptation; Dormancy; Plant growth regulator; Rubus spp